2017
DOI: 10.4049/jimmunol.1601679
|View full text |Cite
|
Sign up to set email alerts
|

Sequence and Phylogenetic Analysis of the Untranslated Promoter Regions for HLA Class I Genes

Abstract: Polymorphisms located within the MHC have been linked to many disease outcomes by mechanisms not yet fully understood in most cases. Variants located within untranslated regions of HLA genes are involved in allele specific expression and may therefore underlie some of these disease associations. We determined sequences extending nearly 2kb upstream of the transcription start site for 68 alleles from 57 major lineages of classical HLA class I genes. The nucleotide diversity within this promoter segment roughly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
48
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(53 citation statements)
references
References 48 publications
5
48
0
Order By: Relevance
“…The expression profile of each allele is apparently related to both nucleotide variation and different methylation profile . In fact, our data indicate that at least 22 promoter variable sites could modify a potential CpG site (such as rs9260072) and the highly expressing alleles HLA‐A *23 and HLA‐A*24 could present fewer CpG sites. However, in both studies, HLA‐A expression levels were measured in specific cell lines.…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations
“…The expression profile of each allele is apparently related to both nucleotide variation and different methylation profile . In fact, our data indicate that at least 22 promoter variable sites could modify a potential CpG site (such as rs9260072) and the highly expressing alleles HLA‐A *23 and HLA‐A*24 could present fewer CpG sites. However, in both studies, HLA‐A expression levels were measured in specific cell lines.…”
Section: Discussionmentioning
confidence: 78%
“…Previous studies have showed allele‐specific mRNA levels, but closely related sequences presented a divergent expression pattern . The expression profile of each allele is apparently related to both nucleotide variation and different methylation profile .…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…This association was confirmed in a genome‐wide expression quantitative trait analysis of HLA‐C mRNA levels determined by qPCR of peripheral blood mononuclear cell RNA from 273 individuals . Interestingly, the group of HLA‐C alleles that have the highest level of expression ( HLA‐C*01 , *04 , *06 , *12 , and *14 ), all possess the A residue associated with higher promoter activity . Furthermore, a second SNP located 20 bp upstream of the Oct‐1 site was also significantly associated with HLA‐C transcript levels, and this SNP is located within a putative NFAT‐AP1 binding site, suggesting the presence of an enhancer element in this region.…”
Section: Upstream Elementsmentioning
confidence: 99%